PHYSICOCHEMICAL AND ORGANOLEPTIC PROPERTIES OF BEEF RARIT USING DIFFERENT TYPES OF SUGAR - ., Safura; Okarini, I. A.; Sarini, N. P. (Jurnal Peternakan Tropika, 2022)
Rarit is one of the traditional food products typical of the island of Lombok in the form of sliced ????meat seasoned with tamarind, salt and sugar and then dried. This research was conducted to determine the physicochemical and organoleptic properties of beef ribs using different types of sugar. In this study, the experimental design used was a completely randomized design (CRD) with four treatments and four replications in order to obtain 16 experimental units. The four treatments were: (P0) 100 grams of beef (abdomen) without treatment or control, (P1) With tamarind, salt and 10 grams of palm sugar treatment, (P2) With tamarind treatment, salt and 10 grams of granulated sugar. and (P3) With tamarind treatment, salt, 10 grams of sugar and palm sugar (5 grams of granulated sugar and 5 grams of palm sugar). The variables observed were physicochemical (cooking loss, pH and water content) and organoleptic quality (taste, aroma, texture and color). The results of the research on physicochemical properties showed significantly different results (P<0.05) against (cooking loss, pH and water content), while on organoleptic (taste, aroma, texture and color) were not significantly different (P>0.05). Based on the results of the study, it can be concluded that the beef tenderloin which was seasoned with cooking loss, pH and water content were significantly different (P<0.05) with the control, while the organoleptic test was not significantly different (P>0.05).    Keywords: Physicochemistry, organoleptic, beef ribs, sugar treatment